Análisis de equidad en el sistema tributario colombiano 2000 - 2013 - Torres Rusinque, Brayan David (Escuela Colombiana de Ingeniería Julio Garavito, 2016)
En esta investigación se busca mostrar el grado de equidad que posee el sistema tributario colombiano para personas jurídicas, durante el periodo 2000 a 2013. El cálculo se basa en el pago de la tarifa bajo la cual están siendo gravados los sectores de la economía colombiana por separado, para ser comparados entre si y lograr una correcta estimación

In this investigation one seeks to show the degree of equity that possesses the tributary Colombian system for legal persons, during the period 2000 2013. The calculation is based on the payment of the rate under which there are being burdened the sectors of the Colombian economy separately, to be compared between it and to achieve a correct estimation
Keywords: Equidad tributaria; Equidad horizontal y vertical; Sistema tributario optimo; Impuesto optimo; Reformas tributarias; Ideal tax; Horizontal and vertical equity; Tributary equity tributary reforms; Tributary reforms; Tributary ideal system